PENGEMBANGAN PENDIDIKAN ISLAM MULTIKULTURAL DI ERA MODERN - Ainur Rofiq; Evi Fatimatuzhuro (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam Universitas Islam Malang, 2019)
Every country, region, topography or appearance form of an area influences the pattern of life of its people, and also influences their way of life, let alone Indonesia which has thousands of islands, various tribes, ethnicities, languages, cultures, even religions. This also makes the customs and culture of society different, culture is created because of human existence. It is human beings who can shape their own culture and the people themselves who use that culture as well, therefore culture will always exist and develop along with the existence and development of humans in each region. Diversity in society is a necessity that cannot be separated from Indonesian national identity. diversity can be said to be the spirit and identity of the community which is a reference to the orientation of values, norms, rules, and guidelines for the daily behavior of members of society in living in groups and in personal life. Then the position of multicultural educators is essential in Islamic education that will be able to answer a problem that has been divided so far due to differences in ethnicity, language, religion, and culture. This multicultural education will be able to glue and also unite the differences of the people of a nation, especially this beloved Indonesian nation, which in fact has and has a variety of ethnic, ethnic, religious, linguistic and cultural communities. Kata Kunci: Development, Multikultural, Modern